Annual ryegrass (Lolium rigidum Gaud) competition altered wheat grain quality: A study under elevated atmospheric CO2 levels and drought conditions. (15th March 2019) - Fernando, Nimesha; Florentine, Singarayer K.; Naiker, Mani; Panozzo, Joe; Chauhan, Bhagirath S.
Highlights: Wheat and annual ryegrass were grown with two [CO2 ], and two water levels. Grain yield, protein content, total grain reducing power and phenolics were measured. Annual ryegrass competition increased wheat grain protein content under both [CO2 ]. Grain yield decreased (by 35%) with annual ryegrass competition. Total grain reducing power and phenolic content were significantly altered by both treatments. Abstract: Annual ryegrass is one of the most serious, costly weeds of winter cropping systems in Australia. To determine whether its competition-mediated plant defence mechanisms effect on wheat grain quality, wheat (cv. Yitpi) and annual ryegrass were grown under two levels of CO2 (400 ppm; (a[CO2 ]) vs 700 ppm; (e[CO2 ]), two levels of water (well-watered vs drought) and two types of competition (wheat only; (W), and wheat × annual ryegrass; (W × R) with four replicates. The competition × [CO2 ] interaction had a significant effect on wheat grain protein content, where it was increased in W × R under both e[CO2 ] (+17%) and a[CO2 ] (+21%). Grain yield, total grain reducing power and phenolic content were significantly affected by [CO2 ] × drought × competition. In a summary, annual ryegrass competition significantly altered the wheat grain quality under both [CO2 ] levels (depending on the soil water level), while also decreasing the grain yield.